Development of a 45K pepper GBTS liquid-phase gene chip and its application in genome-wide association studies - Li, Zixiong; Jia, Zhiqi; Li, Jisuo; Kang, Dongmu; Li, Mingxuan; Ma, Shijie; Cheng, Qing; Shen, Huolin; Sun, Liang (Frontiers in Plant Science, 2024)
Pepper (Capsicum spp.) is a vegetable that is cultivated globally and has undergone extensive domestication, leading to a significant diversification in its agronomic traits. With the advancement of genomics in pepper and the reduction in sequencing costs, the high-throughput detection of single nucleotide polymorphisms (SNPs) and small insertions-deletions (indels) has become increasingly critical for analyzing pepper germplasm and improving breeding programs. As a result, there is a pressing need for a cost-effective, high-throughput, and versatile technique suitable for both foreground and background selection in pepper breeding. In response to this need, our study has developed a 45K pepper Genotyping-By-Target-Sequencing (GBTS) liquid-phase gene chip employing the GenoBaits platform. This chip is composed of 45,389 probes, of which 42,535 are derived from core polymorphic sites (CPS) in the background genetic landscape, while 2,854 are associated with foreground agronomic traits, spanning across 43 traits. The CPS probes are spaced at an average interval of 68 Kb. We have assessed the performance of this chip on 420 pepper germplasms, with successful capture of target DNA fragments by 45,387 probes. Furthermore, the probe capture ratio surpassed 70% in 410 of the 420 germplasms tested. Using this chip, we have efficiently genotyped 273 germplasms for spiciness levels and elucidated the genetic relationships among 410 pepper germplasms. Our results allowed for precise clustering of sister lines and C. chinense germplasms. In addition, through a genome-wide association study (GWAS) for helical fruit shape, we identified three quantitative trait loci (QTLs): heli2.1, heli11.1, and heli11.2. Within the heli11.1 QTL, a gene encoding the tubulin alpha chain was identified, suggesting its potential role in the helical growth pattern of pepper fruits. In summary, the 45K pepper GBTS liquid-phase gene chip offers robust detection of polymorphic sites and is a promising tool for advancing research into pepper germplasm and the breeding of new pepper varieties.